Efektivitas Pembelajaran Pendidikan Agama Islam dan Budi Pekerti dengan Menggunakan Metode Card Sort dalam Meningkatkan Hasil Belajar Siswa Kelas V SD Islam Plus Ummul Mukminin - Fadilla Ulya Tahani; Enoh; Helmi Aziz (UNISBA Press, 2024)
Abstract. Fadilla Ulya Tahani. 10030120192. Effective learning methods encourage students to be actively involved in the learning process. Students have an active role in building their knowledge and understanding to achieve better learning outcomes. This research aims to: 1) obtain an overview of the condition of class V students in Islamic Religious Education and Character Learning before using the Card Sort learning method; 2) analyze the implementation of the Card Sort learning method in class V Islamic Religious Education and Character learning; 3) examine the effectiveness of the Card Sort learning method in improving student learning outcomes in Islamic Religious Education and Character learning. This research was conducted at SD Islam Plus Ummul Mukminin class V with the aim of determining the effectiveness of student learning outcomes after using the Card Sort method in the subjects of Islamic Religious Education and Character. This research uses a quantitative approach with a quasi-experimental method in the form of a Nonequivalent Control Group Design design. The type of sampling uses Nonprobability Sampling or nonrandom sample selection because there are special considerations. In the results of the research involving the experimental class V B and the control class V A. Student learning outcomes improved after implementing learning using the Card Sort method, the learning outcomes reached an average result before (56.81) after (87.48), so it can It was concluded that student learning outcomes in the subjects of Islamic Religious Education and Character had improved after learning using the Card Sort method. The difference in average learning outcomes between the experimental class and the control class is proven by the results of analysis via the t-test showing that the calculated t value = 10,699 > t table, namely 2,080 with a significance level of 95% with a = 0.05. Thus it can be stated that the alternative hypothesis (Ha) is accepted and the null hypothesis (H0) is rejected, which means that there is a difference in the average PreTest and PostTest in the Experiment and Control classes using the Card Sort method which provides an increase in student learning outcomes in Islamic Religious Education subjects. and Characteristics of fifth grade students at SD Islam Plus Ummul Mukminin. Abstrak. Fadilla Ulya Tahani. 10030120192. Metode pembelajaran efektif mendorong siswa untuk terlibat secara aktif dalam proses pembelajaran. Siswa memiliki peran aktif dalam membangun pengetahuan dan pemahaman mereka untuk pencapaian hasil belajar yang lebih baik. Penelitian ini bertujuan untuk: 1) memperoleh gambaran tentang kondisi siswa kelas V dalam Pembelajaran Pendidikan Agama Islam dan Budi Pekerti sebelum menggunakan metode pembelajaran Card Sort; 2) menganalisis Implementasi metode pembelajaran Card Sort pada pembelajaran Pendidikan Agama Islam dan Budi Pekerti kelas V; 3) mengkaji efektivitas metode pembelajaran Card Sort dalam meningkatkan hasil belajar siswa pada pembelajaran Pendidikan Agama Islam dan Budi Pekerti. Penelitian ini dilakukan di SD Islam Plus Ummul Mukminin kelas V yang bertujuan untuk mengetahui adanya efektivitas hasil belajar siswa setelah menggunakan metode Card Sort pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti. Penelitian ini menggunakan pendekatan kuantitatif dengan metode quasi eksperimen dengan bentuk desain Nonequivalent Control Grup Desain. Jenis pengambilan sampel menggunakan Nonprobability Sampling atau pemilihan sampel nonrandom karena ada pertimbangan khusus. Dalam hasil penelitian melibatkan kelas eksperimen V B dan kelas kontrol V A. Hasil belajar siswa mendapati peningkatan setelah dilaksanakannya pembelajaran menggunakan metode Card Sort, pada hasil belajar tersebut mencapai hasil rata-rata sebelum (56,81) setelah (87,48), sehingga dapat disimpulkan hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti mendapati peningkatan setelah dilaksanakannya pembelajaran memakai metode Card Sort. Adapun perbedaan rata-rata hasil belajar antara kelas eksperimen dan kelas kontrol dibuktikan dengan hasil analisis melalui Uji-t menunjukan bahwa nilai t hitung = 10.699 > t tabel yaitu 2.080 dengan taraf signifikansi 95% dengan a = 0,05. Dengan demikian dapat dinyatakan bahwa hipotesis alternatif (Ha) diterima dan hipotesis nihil (H0) ditolak, yang artinya terdapat perbedaan rata-rata PreTest dan PostTest di kelas Eksperimen dan Kontrol dengan menggunakan metode Card Sort memberikan peningkatan hasil belajar siswa pada mata pelajaran Pendidikan Agama Islam dan Budi Pekerti siswa kelas V SD Islam Plus Ummul Mukminin.